1989
DOI: 10.1073/pnas.86.14.5626
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus subgenomic minus-strand RNAs and the potential for mRNA replicons.

Abstract: The genome of the porcine tanmisible gastroenteritis coronavirus is a plus-stand, polyadenylylated, infectious RNA molecule of "'20 kilobases. During virus replication, seven subgenomic mRNAs are generated by what is thought to be a leader-primng mensm to form a 3'-coterminal nested set. By using radiolabeled, strand-specifc, synthetic oligodeoxynucleotide probes in RNA blot hybridization analyses, we have found a minus-strand counterpart for the genome and for each subgenomic mRNA species in the cytoplasm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
310
6
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(339 citation statements)
references
References 36 publications
(20 reference statements)
22
310
6
1
Order By: Relevance
“…In vivo, it is questionable whether hnRNP A1 would have access to the negative-strand IGS, because intracellular negative-strand MHV RNA is entirely duplexed with its positive-strand counterpart (37), which is at least 10-fold more abundant (8). Additionally, elegant work with an infectious clone of the arterivirus equine arteritis virus has shown that if the IGS consensus sequence, in this case the five nucleotides 5Ј-UCAAC-3Ј, was completely changed at a given IGS to 5Ј-AGUUG-3Ј, then synthesis of the corresponding sgRNA was abolished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, it is questionable whether hnRNP A1 would have access to the negative-strand IGS, because intracellular negative-strand MHV RNA is entirely duplexed with its positive-strand counterpart (37), which is at least 10-fold more abundant (8). Additionally, elegant work with an infectious clone of the arterivirus equine arteritis virus has shown that if the IGS consensus sequence, in this case the five nucleotides 5Ј-UCAAC-3Ј, was completely changed at a given IGS to 5Ј-AGUUG-3Ј, then synthesis of the corresponding sgRNA was abolished.…”
Section: Discussionmentioning
confidence: 99%
“…1B). However, the exact nature of the discontinuous leader-body fusion step, whether it occurs during positive-strand or negative-strand RNA synthesis, and the significance of the negative-strand counterparts of the sgRNAs are all matters of controversy (8)(9)(10).…”
mentioning
confidence: 99%
“…However, the rules that determine the joining of the 5' leader to the bodies of the subgenomic mRNAs are not fully understood (Lai, 1990;Makino et al, 1991 ;Jeong & Makino, 1992;La Monica et al, 1992). Furthermore, the discoveries of subgenomic negative strands in coronavirus-infected cells (Hoffmann et al, 1990;Sawicki & Sawicki, 1990;Sethna et al, 1989) and of subgenomic mRNAs in purified virions (Sethna et al, 1989) suggest that the formation of the subgenomic mRNAs may be more complex than initially postulated and may involve the independent replication of the subgenomic mRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…This implies that coronavirus subgenomic RNAs may function as replicons (Sawicki & Sawicki, 1990;Sethna et al, 1989), although the possibility of negativestranded, subgenomic dead-end products (Jeong & Makino, 1992) remains to be excluded.…”
Section: Bev Genome Transcription and Expressionmentioning
confidence: 99%